Transgenic overexpression of ITGB6 in intestinal epithelial cells exacerbates dextran sulfate sodium‐induced colitis in mice. Issue 5 (24th January 2021) - Chen, Haiyan; Chen, Liubo; Wang, Xin; Ge, Xiaoxu; Sun, Lifeng; Wang, Zhanhuai; Xu, Xiaoming; Song, Yongmao; Chen, Jing; Deng, Qun; Xie, Haiting; Chen, Ting; et al.
Abstract: Integrins, as a large family of cell adhesion molecules, play a crucial role in maintaining intestinal homeostasis. In inflammatory bowel disease (IBD), homeostasis is disrupted. Integrin αvβ6, which is mainly regulated by the integrin β6 subunit gene (ITGB6), is a cell adhesion molecule that mediates cell‐cell and cell‐matrix interactions. However, the role of ITGB6 in the pathogenesis of IBD remains elusive. In this study, we found that ITGB6 was markedly upregulated in inflamed intestinal tissues from patients with IBD. Then, we generated an intestinal epithelial cell‐specific ITGB6 transgenic mouse model. Conditional ITGB6 transgene expression exacerbated experimental colitis in mouse models of acute and chronic dextran sulphate sodium (DSS)‐induced colitis. Survival analyses revealed that ITGB6 transgene expression correlated with poor prognosis in DSS‐induced colitis. Furthermore, our data indicated that ITGB6 transgene expression increased macrophages infiltration, pro‐inflammatory cytokines secretion, integrin ligands expression and Stat1 signalling pathway activation. Collectively, our findings revealed a previously unknown role of ITGB6 in IBD and highlighted the possibility of ITGB6 as a diagnostic marker and therapeutic target for IBD.